Bleaching Effect of Ozonized Substances on Resin Composite: A New Potentiality for Ozone Therapy in Dentistry - Simone Gallo; Marco Colombo; Claudio Poggio; Andrea Scribante; Matilda Saracino; Riccardo Beltrami (Applied Sciences, 2023)
Composite resins are commonly used in dentistry for direct restorations. The color stability of these materials still represents a major concern for both the clinician and the patient. In recent years, ozone therapy has been extensively used in dentistry to manage wounds healing, dental caries, oral lichen planus, gingivitis and periodontitis, halitosis, osteonecrosis of the jaw, post-surgical pain, plaque and biofilms, root canal treatment, dentin hypersensitivity, temporomandibular joint disorders, and teeth whitening. To date, several studies have evaluated the bleaching effect exerted by ozone on natural teeth, but no studies have been conducted to determine the effect on the color of composite resins. The aim of the present study is to determine whether ozonized oils/gels could determine a color change on composite resin. A total of 40 discs of an A3 shade restorative composite were divided into two groups, respectively exposed to a pigmentation treatment consisting of 10 applications of 10 min each of a 1% chlorhexidine-based gel (trial group) and to storage into physiological solution (control group). The samples of both groups were respectively subdivided into four subgroups which underwent four different protocols, three of which were based on the exposure to different ozonized products and the latter representing the control. A colorimetric analysis with the CIELAB method was conducted with the following timing: after 24 h of storage in physiological solution (before the experimental procedures) (T0), after the subdivision into groups A and B (corresponding to the pigmentation for samples of group A and storage in physiological solution for samples of group B) (T1), and after subdivision into subgroups 1–4 (corresponding to the application of the ozonized products vs. control) (T2). No statistically significant difference was found between the samples at T0. The 20 samples of group A, exposed to the colorant agent, underwent a color change from T0 to T1, whereas the 20 samples exposed to the physiologic solution did not undergo any significant color change. A positive but moderate influence was assessed for E and L values, whereas no significant change occurred for A and B values. Therefore, dental ozonized oils/gels could be valuable in restorative dentistry as bleaching agents of resin composites exposed to discoloration, an alternative to the traditional hydrogen peroxide and carbamide peroxide, but further studies are required to confirm these findings.